The global status of research in breast cancer liver metastasis: a bibliometric and visualized analysis. Issue 2 (20th December 2021) - Shi, Yanlong; Wei, Wei; Li, Li; Wei, Qian; Jiang, Fei; Xia, Guozhi; Yu, Hongzhu
ABSTRACT: This study aimed to investigate the distribution laws and research frontiers of international literature, so as to present a holistic bibliometric evaluation of the studies on breast cancer liver metastasis(BCLM). Data were collected from the Web of Science Core Collection database, including publications, year, country, journal, author and keywords. The software VOSviewer and CiteSpace were used for bibliometric coupling, co-authorship, co-citation and co-occurrence analysis. In total, 1, 031 publications were analyzed from 2004 to 2020 on BCLM. The year with the highest number of publications was 2006, with 103 papers. The United States, followed by China and Germany were the leading countries on BCLM, accounting for 59% of the whole. The journals that published about BCLM were mainly located in Q1/Q2. Keywords co-occurrence analysis divides BCLM into five clusters:'basic research', 'auxiliary diagnosis and therapy', 'liver resection', 'clinical trial' and 'prognosis'. Main treatment therapies were the latest focus. Burst detection indicated that the trends in BCLM concentrated on subtype and SEER. There is apparently brighter perspective for BCLM research in the coming years, especially in liver resection, subtype and bioinformatics. The consequence of our study as the exclusive scientific evaluation offered an integral overview of BCLM, particularly for research focus and future directions, which can further accurately guide scholars on diagnosis, treatment, and personalized prevention.